Istiqāmah sebagai Paradigma Integrasi Iman dan Amal dalam Tafsir al-Mishbah Karya Quraish Shihab - Juliana Syarah Padang; Sugeng Wanto; Wahyu Wiji Utomo (Yayasan Albahriah Jamiah Indonesia, 2026)
Contemporary Islamic discourse often presents a dichotomy between faith as a realm of belief and deeds as ethical practice, leading to a fragmented religious experience. An integrative framework is required to link the two consistently, and the concept of istiqāmah offers a normative and practical orientation that maintains the continuity of faith and deeds. This study aims to examine the role of istiqāmah in integrating faith and deeds within Quraish Shihab’s Tafsir al-Mishbah. A qualitative, library-based approach was employed using the thematic exegesis (mawḍūʻī) method, involving an interpretive analysis of verses containing the term istiqāmah and its relationship to faith and deeds. The findings reveal three key points: first, istiqāmah is conceptualized as sustained steadfastness encompassing cognitive, affective, and practical dimensions, thereby transcending the mere meaning of ritual consistency. Second, the relationship between faith and deeds in Tafsir al-Mishbah is structurally positioned as an organic unity, wherein faith serves as the foundational value and deeds function as the operational manifestation. Third, istiqāmah acts as an integrative mechanism that stabilizes the relationship between the two through self-control, goal orientation, and sustained action, thereby preventing the disintegration of belief and practice. The theoretical implications underscore the study’s contribution to the development of thematic exegesis, emphasizing conceptual integration and the reinforcement of a holistic, sustainable religious paradigm.